Resistência à corrosão das fases presentes em amálgamas dentários - Acciari, Heloisa Andréa [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Brett, Christopher M. A. (Editora Unesp, 2001)
Neste trabalho avaliou-se a resistência à corrosão em solução salina das fases presentes na microestrutura de amálgamas dentários comerciais: gama1-Ag2Hg3, o eutético Ag-Cu e gama2-Sn7-8Hg, empregando-se técnicas eletroquímicas de potencial a circuito aberto com o tempo, de polarização potenciodinâmica e de espectroscopia de impedância eletroquímica. As ligas metálicas em estudo já foram caracterizadas em um trabalho prévio, por meio de microscopia eletrônica de varredura e difratometria de raios X. A resistência à corrosão se origina da formação de filmes passivos na superfície metálica e parece estar determinada pela natureza rugosa e porosa das superfícies.

In this work, the corrosion resistance behavior of three of their phases presents in dental amalgam has been investigated: gamma1-Ag2Hg3 (the matrix phase in the microstructure), gamma2-Sn7-8Hg (the phase most susceptible to corrosion in the oral cavity, according to the literature) and Ag-Cu eutectic (the component of the more modern powder alloys, the objective being to reduce the quantity of gamma2-Sn7-8Hg formed during the amalgamation and in this way increase its corrosion resistance). Electrochemical measurements were carried out in 0,9% aqueous sodium chloride in order to simulate the aggressivity of the oral cavity, using open circuit potential measurements, polarization curves and electrochemical impedance. The corrosion resistance exhibited by alloys can be associated with formation of a corrosion layer and seems to be dominated by the presence of a porous layer in the surface.
Corrosion resistance of the phases presents in dental amalgams
Keywords: amálgamas dentários; corrosão em meio de cloreto; polarização potenciodinâmica; espectroscopia de impedância eletroquímica; dental amalgam; chloride corrosion; potentiodynamic polarization; electrochemical impedance spectroscopy (EIS)